Overexpression of long non-coding RNA urothelial carcinoma associated 1 causes paclitaxel (Taxol) resistance in colorectal cancer cells by promoting glycolysis. (21st September 2021) - Shi, Huijuan; Li, Kejun; Feng, Jinxin; Zhang, Xiangliang
Abstract : Some colorectal cancer patients show resistance to conventional chemotherapeutic agents including Taxol. This study investigated the roles of lncRNA urothelial carcinoma-associated 1 (UCA1) in the modulation of Taxol resistance in human colorectal cancer cells. According to our results, UCA1 was significantly upregulated in colon cancer cell lines/tissues. Construction of the UCA1 overexpression vector revealed that high UCA1 expression was responsible for Taxol resistance and that Taxol can induce UCA1 expression. Importantly, Taxol-resistant cells had a higher glycolysis rate and upregulated expression of the key glycolysis enzymes hexokinase 2 (HK2) and lactate dehydrogenase A (LDHA) than Taxol-sensitive cells. Further research demonstrated that UCA1 could directly regulate glycolysis by regulating HK2 and LDHA expression, which contributes to Taxol resistance. UCA1 is a potential target to overcome chemoresistance in colorectal cancer. We report the modulation of UCA-1-regulated glycolysis as a novel anticancer strategy along with the novel role of UCA1 in Taxol resistance.